Severe dengue in the intensive care unit - Alexandre Mestre Tejo; Debora Toshie Hamasaki; Letícia Mattos Menezes; Yeh-Li Ho (Journal of Intensive Medicine, 2024)
Dengue fever is considered the most prolific vector-borne disease in the world, with its transmission rate increasing more than eight times in the last two decades. While most cases present mild to moderate symptoms, 5% of patients can develop severe disease. Although the mechanisms are yet not fully comprehended, immune-mediated activation leading to excessive cytokine expression is suggested as a cause of the two main findings in critical patients: increased vascular permeability that may shock and thrombocytopenia, and coagulopathy that can induce hemorrhage. The risk factors of severe disease include previous infection by a different serotype, specific genotypes associated with more efficient replication, certain genetic polymorphisms, and comorbidities such as diabetes, obesity, and cardiovascular disease. The World Health Organization recommends careful monitoring and prompt hospitalization of patients with warning signs or propensity for severe disease to reduce mortality. This review aims to update the diagnosis and management of patients with severe dengue in the intensive care unit.